Projeto de controladores PID para sistemas de segunda ordem sujeitos a retardo variante no tempo - Elder Pereira Fenili (2015)
This thesis presents a methodology for PID controllers tuning (Proportional, Integral and Derivative) for second order systems subject to time-varying delay. The method is based on the Lyapunov-Krasovskii theory. Such theory, takes into account the choice of an appropriate functional, which allows treating stability problems on systems subject to time-delay. In this work was chosen a functional which has exponential terms, so a convergence rate, pre-defined by the designer, can be imposed on the system. The problem is formulated by Linear Matrix Inequalities (LMIs), such that computational tools can be used to find the gains of the controller quite efficiently. Numerical experiments reveal that the method is robust to the variation in time-delay, and the variation of system damping factor. The results with the controller obtained from the proposed method were compared with other methods in the literature. It was observed the new method superiority from the integral of the error performance analysis and transient response of the system when subjected to a step in the reference and a disturbance in the system output.